Tổng hợp nano TiO2 cấu trúc anatase pha tạp neodymium bằng phương pháp sol-gel - Sơn, Vũ Hồng; Sơn, Lê Phúc (Vietnam Journal of Chemistry, 2014)
A series of photo catalysts Nd/TiO2 powders have been prepared by the sol–gel technique with neodymium nitrate and tetra-n-butyl titanium as raw materials, and their characteristics evaluated by X-ray diffraction (XRD), UV–Vis diffuse reflectance spectra (UV–Vis), scanning electron microscopy (SEM). SEM photograph showed that Nd/TiO2 were about 50 nm in diameter. Neodymium doped TiO2 has obvious absorption in the visible light. The catalytic efficiency was tested by monitoring the photo-catalytic conversion of CO in visible light. The results showed that when the doping content was 0.4 % Nd mass, the conversion of CO achieved at 83 %. Keywords: Anatase TiO2, Neodymium doping, photo-catalytic, visible light.